Garden-Mind: A Community Based Non-Formal Education Model through Hydroponic Therapeutic Gardening for Student Development at LPKA Bandung - Hendriano Meggy; Nita Nitiya Intan Tanbrin; Selfiyani Lestari; Kholifatul Novita Ningsih; Kayla Athaya Kaerunnisa; Intan Nurul Azkiy Azkiya; Widya Annisa Sari; Khairunnisa Kamilah (Yayasan Pendidikan Bima Berilmu, 2026)
Student affairs services in non-formal education, particularly in Indonesian juvenile correctional institutions (Lembaga Pembinaan Khusus Anak, LPKA), have yet to fully integrate a community-based education approach, leading to fragmented and reactive service delivery. This study aimed to design, implement, and evaluate the Garden-Mind program as a community-based management model of student affairs that integrates hydroponic-based therapeutic gardening with group guidance and counseling at the Class II Juvenile Correctional Institution of Bandung. Employing a participatory action research approach with a pre–post intervention design, the program ran for eight weeks (16 ninety-minute sessions) involving 15 purposively selected juvenile residents. Data were collected through the Zung Self-Rating Anxiety Scale (ZUNG-SAS), the Perceived Stress Scale (PSS-10), learner journals, structured observation, and focus group discussions, and were analysed using the Wilcoxon signed-rank test (with effect-size r) and six-phase thematic analysis. Findings indicate a significant reduction in anxiety scores (28.4%; r = 0.87, large effect) and stress scores (31.7%; r = 0.89, large effect), with p < 0.001. Qualitative analysis identified four themes of transformation: learner ownership, cohesive learning community, contextual life skills, and positive future orientation. The study theoretically contributes the Model of Community-Based Student Affairs Service Development (MPLSBC) as an integrative managerial framework and practically recommends repositioning LPKA student affairs services from a reactive stance toward a measurable, replicable, and equitable community-based framework that may be standardized across juvenile correctional institutions in Indonesia.